Hourly peak concentration measuring the PM2.5-mortality association: Results from six cities in the Pearl River Delta study. (July 2017) - Lin, Hualiang; Ratnapradipa, Kendra; Wang, Xiaojie; Zhang, Yonghui; Xu, Yanjun; Yao, Zhenjiang; Dong, Guanghui; Liu, Tao; Clark, Jessica; Dick, Rebecca; Xiao, Jianpeng; Zeng, Weilin; et al.
Abstract: Compared with daily mean concentration of air pollution, hourly peak concentration may be more directly relevant to the acute health effects due to the high concentration levels, however, few have analyzed the acute mortality effects of hourly peak levels of air pollution. We examined the associations of hourly peak concentration of fine particulate matter air pollution (PM2.5 ) with mortality in six cities in Pearl River Delta, China. We used generalized additive Poisson models to examine the associations with adjustment for potential confounders in each city. We further applied random-effects meta-analyses to estimate the regional overall effects. We further estimated the mortality burden attributable to hourly peak and daily mean PM2.5 . We observed significant associations between hourly peak PM2.5 and mortality. Each 10 μg/m3 increase in 4-day averaged (lag03 ) hourly peak PM2.5 corresponded to a 0.9% [95% confidence interval (CI): 0.7%, 1.1%] increase in total mortality, 1.2% (95% CI: 1.0%, 1.5%) in cardiovascular mortality, and 0.7% (95% CI: 0.2%, 1.1%) in respiratory mortality. We observed a greater mortality burden using hourly peak PM2.5 than daily mean PM2.5, with an estimated 12915 (95% CI: 9922, 15949) premature deaths attributable to hourly peak PM2.5, and 7951 (95% CI: 5067, 10890) to daily mean PM2.5 in the Pearl River Delta (PRD) region during the study period. This study suggests that hourly peak PM2.5 might be one important risk factor of mortality in PRD region of China; the finding provides important information for future air pollution management and epidemiological studies. Graphical abstract: Highlights: We observed an association between hourly peak PM2.5 and mortality. A 10 μg/m3 increase in PM2.5 corresponded to 0.9% all cause mortality increase. About 3.7% of all-cause mortalities were attributable to hourly peak PM2.5 .